Effects of exercise therapy on patients with poststroke cognitive impairment: A systematic review and meta-analysis - Zhang, Yuanxing; Qiu, Xichenhui; Chen, Jinghao; Ji, Cuiling; Wang, Fang; Song, Dan; Liu, Caiyan; Chen, Lu; Yuan, Ping (Frontiers in Neuroscience, 2023)
Objective To evaluate the effects of exercise therapy on patients with poststroke cognitive impairment and compare the differences in the effect of this method when compared with conventional measures, providing evidence for a more standardized and effective clinical application of exercise therapy. Methods A search was conducted using 7 electronic databases, including PubMed, CINAHL, Web of Science, CENTRAL, CNKI, Wanfang, SinoMed, and clinical trials registry platforms for randomized controlled trials concerning exercise therapy on patients with poststroke cognitive impairment. Two researchers independently screened the literature, evaluated the quality, and extracted information. Meta-analysis was carried out using Review Manager 5.4 software. Results There were 11 studies with 1,382 patients. Meta-analysis showed that exercise therapy could improve cognitive function [SMD = 0.67, 95% CI (0.31, 1.04), P = 0.0003], motor function [SMD = 1.81, 95% CI (0.41, 3.20), P = 0.01], and the activities of daily living [MD = 8.11, 95% CI (3.07, 13.16), P = 0.002] in patients with poststroke cognitive impairment. Conclusion Exercise therapy can not only improve cognitive function in patients with poststroke cognitive impairment but also improve motor function and the activities of daily living. Medical staff should prioritize the management of patients with poststroke cognitive impairment and carry out exercise therapy actively to improve the cognitive function of patients with stroke. Systematic review registration https://www.crd.york.ac.uk/prospero/, identifier: CRD42023397553.